2022
DOI: 10.1186/s40834-022-00182-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of male involvement in family planning services in Abia State, Southeast Nigeria

Abstract: Background Male involvement in family planning (FP) remains low in male-dominant communities. Family planning contributes to the regulation of fertility and population growth in Nigeria. Increasing male involvement in family planning services is crucial in reducing maternal morbidity and mortality in patriarchal societies such as Nigeria. This study identified the determinants of male involvement in family planning services in Abia State, Nigeria. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In Tanzania, determinants including age (35–54 years), secondary/higher education, middle and rich wealth status, being widowed, working, and having access to media information were predictors of male involvement in FP decisions. Other studies have come out with similar findings [ 25 , 41 , 42 ]. Male decision-making regarding FP is influenced by the socio-cultural context, including individual views and feelings towards male involvement in FP use and decision-making.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In Tanzania, determinants including age (35–54 years), secondary/higher education, middle and rich wealth status, being widowed, working, and having access to media information were predictors of male involvement in FP decisions. Other studies have come out with similar findings [ 25 , 41 , 42 ]. Male decision-making regarding FP is influenced by the socio-cultural context, including individual views and feelings towards male involvement in FP use and decision-making.…”
Section: Discussionsupporting
confidence: 81%
“…This has decreased the effects of FP interventions and coupled with uncontrolled fertility, which impedes economic growth and throws a nation’s politics into instability [ 39 , 40 ]. Studies on FP have found that male involvement is positively correlated with access to the media, including television and radio, spouse employment status, and average monthly income [ 41 , 42 ]. Despite this, there are conflicting results regarding the level of male involvement in FP decisions and the factors that influence this involvement in Malawi and Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Unmet family planning needs in women apply to those who are married or in unions, fecund and are sexually active, who want to stop childbearing or delay their next birth by at least two years, but are not using any method of contraception, either modern or traditional (DHS, 2014). However, this definition can be misleading as several studies have reported that male partner involvement and preferences have played a major role in such decision-making [9][10][11]. For example, studies have shown that male dominance in Africa greatly affects women's ability to access and use any form of contraceptives [12].…”
Section: Introductionmentioning
confidence: 99%